Theory of structural formation in Anthony Giddens (an attempt to reconcile structure and action in understanding human society) an analytical- critical study - Fayad, Hossam Aldin Mahmoud (Journal of Humanities & Social Sciences, 2020)
The study aimed to clarify the theoretical and methodological foundations of the theory of structural formation in Giddens, to achieve a systematic integration between structure and action in understanding the nature of human behavior, and the study relied on the analytical- critical approach in analyzing and interpreting the subject of the study, and the study also concluded that the individuals are the ones who make up the society, And at the same time, society is re-establishing them. That is, social patterns resemble buildings, where they can be rebuilt with the same stones that were built continuously. This is evidence of societies continuing to evolve from state to state until the stage of annihilation and dissolution. In the end, the study recommended researchers in the field of social sciences to stay away from adopting theoretical approaches Traditionalism with a unilateral interpretation (Interpretative- structural), and emphasizing the use of dual structure and action in the interpretation of human behavior and understanding the nature of the emergence and dissolution of human communities.
Keywords: theory; structural formation; structure; action; society